DEBATE TECHNOLOGY AS A TOOL FOR DEVELOPMENT OF SPEAKING SKILLS - Balzhanova, А.М.; Fomich, J. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
Speaking as one of the basic skills can help us to express our own ideas and thoughts; therefore, on the basis of increasing students’ speaking skills we open them new ways for their critical thinking and self-development. The article aims to determine the possibility of increasing students` speaking skills through the usage of debate technology.
Keywords: education; critical thinking; debate technology; speaking skills; foreign language